Mitochondrial respiratory chain deficiency inhibits lysosomal hydrolysis. Issue 9 (2nd September 2019) - Fernandez-Mosquera, Lorena; Yambire, King Faisal; Couto, Renata; Pereyra, Leonardo; Pabis, Kamil; Ponsford, Amy H.; Diogo, Cátia V.; Stagi, Massimiliano; Milosevic, Ira; Raimundo, Nuno
ABSTRACT: Mitochondria are key organelles for cellular metabolism, and regulate several processes including cell death and macroautophagy/autophagy. Here, we show that mitochondrial respiratory chain (RC) deficiency deactivates AMP-activated protein kinase (AMPK, a key regulator of energy homeostasis) signaling in tissue and in cultured cells. The deactivation of AMPK in RC-deficiency is due to increased expression of the AMPK-inhibiting protein FLCN (folliculin). AMPK is found to be necessary for basal lysosomal function, and AMPK deactivation in RC-deficiency inhibits lysosomal function by decreasing the activity of the lysosomal Ca 2+ channel MCOLN1 (mucolipin 1). MCOLN1 is regulated by phosphoinositide kinase PIKFYVE and its product PtdIns(3, 5)P2, which is also decreased in RC-deficiency. Notably, reactivation of AMPK, in a PIKFYVE-dependent manner, or of MCOLN1 in RC-deficient cells, restores lysosomal hydrolytic capacity. Building on these data and the literature, we propose that downregulation of the AMPK-PIKFYVE-PtdIns(3, 5)P2 -MCOLN1 pathway causes lysosomal Ca 2+ accumulation and impaired lysosomal catabolism. Besides unveiling a novel role of AMPK in lysosomal function, this study points to the mechanism that links mitochondrial malfunction to impaired lysosomal catabolism, underscoring the importance of AMPK and the complexity of organelle cross-talk in the regulation of cellular homeostasis. Abbreviation : ΔΨm : mitochondrial transmembrane potential; AMP: adenosine monophosphate; AMPK: AMP-activated protein kinase; ATG5: autophagy related 5; ATP: adenosine triphosphate; ATP6V0A1: ATPase, H+ transporting, lysosomal, V0 subbunit A1; ATP6V1A: ATPase, H+ transporting, lysosomal, V0 subbunit A; BSA: bovine serum albumin; CCCP: carbonyl cyanide-m-chlorophenylhydrazone; CREB1: cAMP response element binding protein 1; CTSD: cathepsin D; CTSF: cathepsin F; DMEM: Dulbecco's modified Eagle's medium; DMSO: dimethyl sulfoxide; EBSS: Earl's balanced salt solution; ER: endoplasmic reticulum; FBS: fetal bovine serum; FCCP: carbonyl cyanide-p-trifluoromethoxyphenolhydrazone; GFP: green fluorescent protein; GPN: glycyl-L-phenylalanine 2-naphthylamide; LAMP1: lysosomal associated membrane protein 1; MAP1LC3B/LC3B: microtubule associated protein 1 light chain 3 beta; MCOLN1/TRPML1: mucolipin 1; MEF: mouse embryonic fibroblast; MITF: melanocyte inducing transcription factor; ML1N*2-GFP: probe used to detect PtdIns(3, 5)P2 based on the transmembrane domain of MCOLN1; MTORC1: mechanistic target of rapamycin kinase complex 1; NDUFS4: NADH:ubiquinone oxidoreductase subunit S4; OCR: oxygen consumption rate; PBS: phosphate-buffered saline; pcDNA: plasmid cytomegalovirus promoter DNA; PCR: polymerase chain reaction; PtdIns3P: phosphatidylinositol-3-phosphate; PtdIns(3, 5)P2 : phosphatidylinositol-3, 5-bisphosphate; PIKFYVE: phosphoinositide kinase, FYVE-type zinc finger containing; P/S: penicillin-streptomycin; PVDF: polyvinylidene fluoride; qPCR: quantitative real time polymerase chain reaction; RFP: red fluorescent protein; RNA: ribonucleic acid; SDS-PAGE: sodium dodecyl sulfate polyacrylamide gel electrophoresis; shRNA: short hairpin RNA; siRNA: small interfering RNA; TFEB: transcription factor EB; TFE3: transcription factor binding to IGHM enhancer 3; TMRM: tetramethylrhodamine, methyl ester, perchlorate; ULK1: unc-51 like autophagy activating kinase 1; ULK2: unc-51 like autophagy activating kinase 2; UQCRC1: ubiquinol-cytochrome c reductase core protein 1; v-ATPase: vacuolar-type H+-translocating ATPase; WT: wild-type